Model Penentuan Jumlah Kapal dan Komposisinya untuk Short Sea Shipping Pulau Jawa - Ika Deefi Anna; Fitri Agustina (Institute of Research and Community Outreach - Petra Christian University, 2016)
This research aims to determine the amount and mixture composition of vessels in short sea shipping (SSS) operation in Java. SSS in Java is proposed to mitigate the surface transportation problem and move freight off the overcrowded North-Coast highways and rail systems onto the waterways. A mathematical model based on non-linear integer programming was developed to calculate the amount and the composition mix of vessels required for the proposed system. The model was solved by Lingo software and the computational results reveal that the proposed system would require daily shipment using 1 unit of type B vessel and 1 unit of type C vessel. The calculation results also show that the SSS in Java would require 6 vessels to operate. Overall, the model and the obtained solutions in this paper provide an alternative to raise awareness of short sea shipping’s potential with the government, logistic companies, and executive policymakers. Finally, this paper also contribute to research of maritime fleet size and mix problems.